2020
DOI: 10.1016/j.cell.2020.04.049
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Loss Can Cause Death through Accumulation of Reactive Oxygen Species in the Gut

Abstract: Highlights d Sleep deprivation leads to ROS accumulation in the fly and mouse gut d Gut-accumulated ROS trigger oxidative stress in this organ d Preventing ROS accumulation in the gut allows survival without sleep in flies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
305
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 341 publications
(320 citation statements)
references
References 253 publications
(339 reference statements)
13
305
1
1
Order By: Relevance
“…In all animals studied to date, sleep deprivation causes not just behavioral changes (increased sleep pressure) but also cellular stress (Cirelli and Tononi 2000;Cirelli et al 2005;Naidoo et al 2005;Jones et al 2008), and, in some animals, total sleep deprivation is lethal (Rechtschaffen et al 1983;Shaw et al 2002;Vaccaro et al 2020). In C. elegans too, sleep deprivation results in cell stress, as manifested by movement of DAF-16 into the nucleus (Driver et al 2013;Sanders et al 2017), and by upregulation of markers for ER and mitochondrial proteostatic stress (Sanders et al 2017).…”
Section: Homeostatic Regulation Of Sleepmentioning
confidence: 99%
“…In all animals studied to date, sleep deprivation causes not just behavioral changes (increased sleep pressure) but also cellular stress (Cirelli and Tononi 2000;Cirelli et al 2005;Naidoo et al 2005;Jones et al 2008), and, in some animals, total sleep deprivation is lethal (Rechtschaffen et al 1983;Shaw et al 2002;Vaccaro et al 2020). In C. elegans too, sleep deprivation results in cell stress, as manifested by movement of DAF-16 into the nucleus (Driver et al 2013;Sanders et al 2017), and by upregulation of markers for ER and mitochondrial proteostatic stress (Sanders et al 2017).…”
Section: Homeostatic Regulation Of Sleepmentioning
confidence: 99%
“…Flies were raised on cornmeal-agar medium 71 . Briefly, our regular food contained 7.3% agar (Spectrum), 12.7% yeast (MP Biomedicals), 56% sugar (Domino) and 24% cornmeal (Bunge).…”
Section: Fly Mediamentioning
confidence: 99%
“…In particular, the stress-sensing of intestinal cells regarding peptide production in response to multiple internal and external stimuli is largely unknown. Growing findings of novel stress responses, such as mechanical stress induced by different components in the food ( He et al, 2018 ; Li et al, 2018a ), local hypoxic response caused by bacterial infection ( Valzania et al, 2018 ; Krejcova et al, 2019 ), immune response triggered by intestinal microbial metabolites ( Kamareddine et al, 2018 ), as well as the newly-identified oxidative stress associated with sleep loss ( Vaccaro et al, 2020 ), keep shaping our current understanding of intestinal phenomena. Therefore, integrating multi-reporter system, long-term live imaging ( Martin et al, 2018 ), and scRNAseq to monitor diverse stress responses and study whether and how gut-peptide-hormone production is affected by them will add new dimensions for exploiting gut physiology and metabolic homeostasis ( Figure 4A ).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have revealed that an EC-derived amino acid, D-serine, is essential for sleep control (Dai et al, 2019), indicating a participating role of fly gut. Strikingly, a recent study further demonstrated that sleep deprivation results in accumulation of reactive oxygen species (ROS) and triggers consequent oxidative stress specifically in the gut, whereas diminishment of ROS accumulation in the gut improves survival without sleep in flies (Vaccaro et al, 2020). Given the fact that ROS regulates diverse metabolic signaling pathways, as well as tissue homeostasis and commensal bacterial control, in the gut (Ha et al, 2005;Ayyaz and Jasper, 2013;Xu et al, 2017), we speculate that ROS-associated production and release of gut-peptide hormone might function as a nexus between sleep and metabolic homeostasis and beyond.…”
Section: Other Pathological Conditions and Gut-peptide Hormonesmentioning
confidence: 99%